2010
DOI: 10.1186/1471-2105-11-396
|View full text |Cite
|
Sign up to set email alerts
|

Application of machine learning methods to histone methylation ChIP-Seq data reveals H4R3me2 globally represses gene expression

Abstract: Background In the last decade, biochemical studies have revealed that epigenetic modifications including histone modifications, histone variants and DNA methylation form a complex network that regulate the state of chromatin and processes that depend on it including transcription and DNA replication. Currently, a large number of these epigenetic modifications are being mapped in a variety of cell lines at different stages of development using high throughput sequencing by members of the ENCODE con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
67
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(71 citation statements)
references
References 37 publications
4
67
0
Order By: Relevance
“…Unexpectedly, they did not find any correlation between this mark and transcriptionally repressed loci. However, reevaluation of this data, by a different group, indicated that the H4R3me2s mark is strongly associated with repressed gene expression [103].…”
Section: H4r3me2s and H2ar3me2smentioning
confidence: 95%
“…Unexpectedly, they did not find any correlation between this mark and transcriptionally repressed loci. However, reevaluation of this data, by a different group, indicated that the H4R3me2s mark is strongly associated with repressed gene expression [103].…”
Section: H4r3me2s and H2ar3me2smentioning
confidence: 95%
“…A simple approach for integrating epigenomic and transcriptomic data is to replace the genetic with epigenetic measurements in the regression model [15][16][17]. Stepwise regression procedures were proposed to study interaction effects between different histone modifications that may not act independently on gene transcription [18]. Moreover, various machine learning approaches were applied to predict gene transcription levels based on transcription factor binding, histone modification or other epigenomic data [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…PRMT5 acts as a protein arginine methyltransferase and catalyzes the transfer of two methyl groups symmetrically to the arginine residue of protein substrates. PRMT5 is involved in a variety of biological processes, such as the regulation of gene expression through various mechanisms that include histone modification, chromatin remodeling, mRNA splicing, and protein biosynthesis . PRMT5 also functions in DNA replication and repair, formation of the Golgi apparatus and ribosomes, cell cycle checkpoints, cell migration, cell reprogramming, development, liver metabolism, and the circadian clock …”
mentioning
confidence: 99%